Measurement of Mental Workload Against Packing Operators at UKM Roti Heppy Bakery Padang Using the NASA-TLX Method - Fithri, Prima; Syahfikri, Naufal (Andalasian International Journal of Applied Science, Engineering and Technology, 2021)
In this increasingly advanced era of globalization, more and more manufacturing and service companies are developing which brings intense competition for companies to be able to maintain the company's establishment. IKM Heppy Bakery is one of the bread production companies that is experiencing this competition. For the realization of companies that can compete in the era of globalization, highly competent resources are also needed. The impact of this competition causes more work demands and causes workload effects both physically and mentally on employee performance. Based on this, a mental workload study was conducted to determine the amount of mental workload of employees using the NASA-TLX method. Based on calculations using the NASA-TLX method, it was found that the level of mental workload on bread packaging at IKM Heppy Bakery was included in the very high category with 4 workers having a very high workload category and there were also 2 workers with a high workload category. The average WWL score on bread packaging is 82. For this condition, it is deemed necessary to have an evaluation accompanied by an improvement in the work system or reward to foster motivation and enthusiasm and reduce stress for Heppy Bakery's bread packaging employees.